Regulatory Challenges of Islamic Fintech in Indonesia: A Policy Analysis of the Harmonization of Sharia Principles and Technological Innovation - Kurnia Puspita Wulandari (CV Edujavare Publishing, 2026)
The growth of Islamic financial technology (fintech) in Indonesia presents a paradox that requires serious academic attention. On one hand, Indonesia ranks third in the world on the Global Islamic Fintech Ecosystem Index (GIFT Index) according to the Global Islamic Fintech Report 2024/25, with a market value reaching USD 8.5 billion. On the other hand, only 7.2 percent of licensed peer-to-peer (P2P) lending operators in the country run on Sharia principles. This gap between potential and reality is largely rooted in the complexity and fragmentation of the regulatory framework governing the national Islamic fintech industry. This study aims to map and analyze the existing regulatory framework for Islamic fintech in Indonesia, identify gaps and tensions between the Financial Services Authority (OJK)’s technical regulations and the National Sharia Board of the Indonesian Ulema Council (DSN-MUI)’s normative fatwa standards, and formulate adaptive and comprehensive policy recommendations to achieve harmonization between Sharia principles and technological innovation. This study uses a qualitative approach with a normative legal research method, combining literature review, content analysis, and comparative policy analysis. The findings reveal four main conclusions. First, Indonesia’s Islamic fintech regulatory framework is supported by a dual legal system involving OJK through POJK No. 10/2022 and DSN-MUI through Fatwa No. 117/2018, but the two have not been integrated into a coherent legal framework, resulting in significant policy fragmentation and implementation gaps. Second, the position of DSN-MUI fatwa as merely filling legal vacuums—rather than being directly part of the national legal system as in Malaysia—makes Sharia compliance enforcement highly dependent on the goodwill of industry players, rather than on firm legal sanctions. Third, the tension between the relatively stable nature of Sharia principles and the exponential pace of technological innovation creates unresolved legal grey areas, particularly regarding digital contract validity, blockchain, artificial intelligence, and Sharia-based crypto assets. Fourth, the Sharia Supervisory Board (DPS) as the frontline of Sharia compliance at the entity level faces serious technical capacity limitations in overseeing increasingly complex fintech products.